Emerging treatment options for psoriasis - Taheri A; Sandoval LF; Moradi Tuchayi S; Alinia H; Mansoori P; Feldman SR (Dove Medical Press, 2014)
Arash Taheri,1 Laura F Sandoval,1 Sara Moradi Tuchayi,1 Hossein Alinia,1 Parisa Mansoori,2 Steven R Feldman1–3 1Center for Dermatology Research, Department of Dermatology, 2Department of Pathology, 3Department of Public Health Sciences, Wake Forest School of Medicine, Winston-Salem, NC, USA Abstract: The treatment of psoriasis has evolved over the years, with the recent focus largely on the use of biologics and anti-interleukin-17 agents. With treatment options expanding, practitioners and patients may find control of psoriasis more convenient and safer to achieve. In this article, we review the literature on emerging medications for the treatment of psoriasis. Although some of the new medications under development, such as the anti-interleukin-17 agents, are being shown to be very efficacious in the treatment of psoriasis in premarketing trials, more information regarding their long-term use is needed to demonstrate their superiority over available modalities. Keywords: psoriasis, therapy, interleukin-17, biologics, emerging, treatment